PID controller design for interval load frequency control system with communication time delay. (August 2019) - Sharma, Jitendra; Hote, Yogesh V.; Prasad, Rajendra
Abstract: In load frequency control (LFC), the data from measurements sensors are transmitted from far-off remote terminal units (RTUs) to the controlling center and control signals are transmitted from the controlling center to the plant location. These transmissions of various signals are possible via communication channels which are characterized by constant delays. Modern day power systems are quite complex in the present deregulated environment. This complexity has been further enhanced by the inherent delay introduced by the communication channels. Because of the communication delay, the conventional load frequency control design techniques give unacceptable performance. Further, in case of severe delay, the load frequency control system may become unstable. In view of this, a proportional–integral–derivative (PID) controller is designed using stability boundary locus (SBL) approach for interval single area power system with non-reheated thermal turbine and reheated thermal turbine having communication delay and then the proposed approach is validated on the multi-area IEEE 39-bus New England test system. The simulation results indicate the efficacy of the proposed methodology. Highlights: SBL approach of PID controller design is used for interval LFC system with time delay. PID controller is designed for LFC of single area power system having NRTD and RTD. Frequency changes with load are compared for NRTD and RTD without and with GDB & GRC. Frequency changes are also compared for LFC having NRTD with existing publications. Proposed approach is then validated on interval IEEE 39-bus New England test system.